1990
DOI: 10.1159/000125380
|View full text |Cite
|
Sign up to set email alerts
|

Non-Steroidal Follicular Factors Attenuate the Self-Priming Action of Gonadotropin-Releasing Hormone on the Pituitary Gonadotroph

Abstract: Pituitary glands of pro-oestrous and oestrous rats were perifused in series with isolated ovarian follicles and the luteinizing hormone (LH) and follicle-stimulating hormone (FSH) responses to gonadotropin-releasing hormone (GnRH) were measured. Pituitary glands from pro-oestrous rats, perifused with the effluent medium from isolated preovulatory follicles, showed a significant reduction in the self-priming effect of GnRH as observed from the typical biphasic LH response to a continuous GnRH challenge. The ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 15 publications
1
18
0
1
Order By: Relevance
“…GnSAF is distinct from inhibin (Ying, 1988), a gonadal protein factor which acts primarily by suppressing the basal secretion of FSH (Fowler et al, 1990;Byrne et al, 1995;Mroueh et al, 1996;Pappa et al, 1999a,b). GnSAF bioactivity has been demonstrated, by monitoring changes in the GnRH-induced LH secretion levels of rat pituitary primary cell cultures, in the ovarian follicular¯uid (FF) of human (Busbridge et al, 1990;Fowler et al, 1990;Knight et al, 1990;Mroueh et al, 1996) and other mammalian species (Schenken and Hodgen, 1986;Danforth et al, 1987;Busbridge et al, 1988;Danforth and Cheng, 1995), as well as in culture supernatants from human ovarian granulosa cells (Fowler et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…GnSAF is distinct from inhibin (Ying, 1988), a gonadal protein factor which acts primarily by suppressing the basal secretion of FSH (Fowler et al, 1990;Byrne et al, 1995;Mroueh et al, 1996;Pappa et al, 1999a,b). GnSAF bioactivity has been demonstrated, by monitoring changes in the GnRH-induced LH secretion levels of rat pituitary primary cell cultures, in the ovarian follicular¯uid (FF) of human (Busbridge et al, 1990;Fowler et al, 1990;Knight et al, 1990;Mroueh et al, 1996) and other mammalian species (Schenken and Hodgen, 1986;Danforth et al, 1987;Busbridge et al, 1988;Danforth and Cheng, 1995), as well as in culture supernatants from human ovarian granulosa cells (Fowler et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in the present study, basal concentrations of FSH in the FSH cycles increased in all women from mid-to late luteal phase (Fig. 1) (Busbridge et al, 1990;Fowler et al, 1990a;Knight et al, 1990) and has a molecular mass in the range of 10-30 kDa (Fowler et al, 1992 (McLachlan et al, 1987a, b;Tsonis et al, 1987), GnSAF is produced by the corpus luteum. However, another possibility is that some of the smaller follicles that do not have the capacity to respond to hCG and luteinize continue producing GnSAF during the early luteal phase.…”
Section: Patientsmentioning
confidence: 49%
“…In that respect, the role of GnSAF is not limited to the time of the midcycle LH surge, but is also extended at least to the first half of the cycle when it controls LHRH-induced gonadotrophin release by a negative effect (Messinis and Templeton, 1991a). Several studies using various in vitro bioassay systems have shown activity of GnSAF, distinct from inhibin, in steroid-free human follicular fluid from superovulated and spontaneous cycles (Busbridge et al, 1990;Fowler et al, 1990a;Knight et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Administration of supra-physiological amounts of gonadotrophin-releasing hormone (GnRH) to female rats gives rise to a protein synthesis-dependent increased luteinizing hormone (LH) response of the gonadotrophic cells to GnRH, known as the self-priming process (Edwardson & Gilbert 1975, Pickering & Fink 1976, Waring & Turgeon 1980, Evans et al 1984, Busbridge et al 1990, de Koning 1995, Fink 1995. The LH surge is the only self-priming effect generated by endogenous GnRH in the rat (Gallo 1981a, Padmanabhan et al 1982, Fox & Smith 1985, Allen et al 1988, Kalra 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The antagonistic interaction between GnRH and the ovarian protein, gonadotrophin surge-inhibiting factor or attenuating factor (GnSIF/AF), may be responsible for this tightly controlled LH release (de Koning et al 1979, 1987, 1989, Busbridge et al 1990, Knight et al 1990, Koppenaal et al 1993, Fowler et al 1994, de Koning 1995, van Dieten & de Koning 1995. It was postulated that after each pulse of GnRH, GnSIF/AF neutralizes the potential self-priming action of GnRH before it can become effective, thereby maintaining a state of low LH responsiveness of the gonadotrophs to the action of the next GnRH pulse (de Koning 1995, van Dieten & de Koning 1995.…”
Section: Introductionmentioning
confidence: 99%